The Role of Macrolides in Noncystic Fibrosis Bronchiectasis - Figueiredo, Bruna de Campos Guimarães e; Ibiapina, Cássio da Cunha (Pulmonary Medicine, 2011)
Objective. The present study aims at reviewing the main publications on the use of macrolides as immunomodulators in patients with noncystic fibrosis bronchiectasis. Source of Data. The Medline database was our source of data for this research carried out until June 2011, using the key words: macrolides and bronchiectasis, while searching for original articles and reviews. Summary of Data. Seven clinical studies that evaluated the action of the macrolides in patients with bronchiectasis were found. There was the sputum volume, reduction in pulmonary exacerbation frequency, and in the use of antimicrobial treatment, in addition to pulmonary function improvement. Conclusions. Anti-inflammatory action and immunomodulatory effects can be attributed to macrolides when administered in low doses and on the long term. This use has been well established both in diffuse panbronchiolitis and in cystic fibrosis. Evidence indicates possible benefits in bronchiectasis. Future studies are needed, though, to establish the ideal dose and treatment duration and to understand the implications in the generation of microbial resistance.